Sustainable Rural Development in Iraq - Reality and Challenges for the Period (2018-2022 - Al-Sadoon, Raed (The Gulf Economist, 2024)
The study dealt with the reality of rural development in Iraq, with a focus on the challenges and opportunities available to advance the rural society. With the mention of economic, social and environmental factors affecting rural development, such as infrastructure, agriculture, natural resources, and levels of education and health. It was also highlighted on government policies and development programs applied in rural areas, and the extent of their impact on improving the standard of living for rural population, as well Supporting the small and medium enterprises sector, besides that, population stability is governed by several factors, the most important of which is to provide job opportunities Public services and basic needs play an active role in resettling and stabilizing the population and reducing migration towards urban areas